2013
DOI: 10.1051/cocv/2012042
|View full text |Cite
|
Sign up to set email alerts
|

Global minimizers for axisymmetric multiphase membranes

Abstract: We consider a Canham-Helfrich-type variational problem defined over closed surfaces enclosing a fixed volume and having fixed surface area. The problem models the shape of multiphase biomembranes. It consists of minimizing the sum of the Canham-Helfrich energy, in which the bending rigidities and spontaneous curvatures are now phase-dependent, and a line tension penalization for the phase interfaces. By restricting attention to axisymmetric surfaces and phase distributions, we extend our previous results for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It can also be shown that lipid bilayers present a high level of incompressibility due to the energy penalty associated with areal stretching being significantly higher compared to membrane deformations due to bending (28). This is similar to the approach taken by Choksi et al (29) and Sarasij et al (30).…”
Section: Methodssupporting
confidence: 80%
“…It can also be shown that lipid bilayers present a high level of incompressibility due to the energy penalty associated with areal stretching being significantly higher compared to membrane deformations due to bending (28). This is similar to the approach taken by Choksi et al (29) and Sarasij et al (30).…”
Section: Methodssupporting
confidence: 80%
“…After this work was completed, we became aware of the preprint [19], which studies the Γ-limit of a diffuse-interface approximation of Helfrich's functional for two-phase axisymmetric surfaces, and where many of the same technical difficulties that we encounter are addressed. We are independently treating the sharp-interface case of two-phase axisymmetric surfaces in [11].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…(41),T L has an obvious analogous definition and ∆T c,M are defined by Eqs. (42). By plugging these expressions into (37) and expanding for small differences we get the equation…”
Section: Appendix A: Geodesic Normal Coordinatesmentioning
confidence: 99%
“…in Refs. [37][38][39][40][41][42][43][44], and also by us in Ref. [18]) and appears to be the most popular choice within the mathematics-oriented literature.…”
Section: Introductionmentioning
confidence: 99%